SMAQ a measurement-based tool for traffic modeling and queuing analysis. I. Design methodologies and software architecture. - Li, San-Qi (IEEE Communications magazine)
SMAQ is a measurement-based tool for integration of traffic modeling and queuing analysis. There are three basic components in SMAQ. In the design of the first component, statistic measurement, the most critical issues are to identify the important traffic statistics for queuing analysis in a finite buffer system and then to build a measurement structure to collect them. Our study indicates that both first- and second-order traffic statistics, measured within a given frequency-window, have a very significant impact on the queue length and loss rate performance. In the design of the second component, matched modeling, the focal point is to construct a stochastic model that can match a wide range of important statistics collected in various applications. New methodologies and fast algorithms are developed for such construction on the basis of a circulant modulated Poisson process (CMPP). For the third component, queuing solutions, the basic requirement is to provide numerical solutions of the queue length and loss rate for transport of given traffic in a finite buffer system. A fast and stable computation method, called a Folding algorithm, is applied to provide both steady-state and transient solutions of various kinds, including congestion control performance where arriving traffic are selectively discarded based on queue thresholds. We provide both design methodologies and software architectures of these three components, with discussion of practical engineering issues for the use of the SMAQ tool